KARAKTERISTIK KEPEMIMPINAN KHULAFA AR-RASYIDIN - Iva Inayatul Ilahiyah; Muhammad Nur Salim (EL-Islam, 2019)
This study will discuss the characteristics of the Khulafa Ar-Rasyidin leadership including Abu Bakar As-Shidiq, Umar Bin Khattab, Utsman Bin Affan, and Ali Bin Abi Thalib. The researcher used qualitative research, library research. The researcher used the documentation to collect the data. The results of this study are 1) Characteristics of Abu Bakar’s leadership expanding area to several regions in order to Islamic region wider and it could obtain the protection from several regions. The important even of Abu Bakar‘s leadership is collecting Al Qur’an sentences (ayat which are stated in some different region), it is because many memorized-Qur’an people had been killed on the battlefield. Moreover, it is feared that all the memorizer will be killed, 2) Characteristics of Umar Bin Khattab’s leadership, He always prioritized deliberations in making decision-based on Rasulullah’s track and he never put himself as the ruler, 3) Characteristics of Utsman Bin Affan’s leadership are, he created marine which was motivated by attacks from the Roman army whichfinally could be defeated. In this era, the expansion of Islamic territory was also widespread increasingly by using the same system of government as the Umar’s system in developing natural resources, 4) Characteristics of Ali Bin Abi Thalib’ s leadership, He revived Abu Bakr and Umar’s aspiration to return back all the land and grants that had been distributed by Utsman to his relatives into the government’s ownership. Ali also brought down immediately all governors who were not disliked by the people who were considered as the source of slander and also as the cause of the rise of the rebels who against Utsman.